2013
DOI: 10.1093/ageing/aft112
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and pathological correlates of orthostatic hypotension and its subtypes when measured using beat-to-beat technology in a sample of older adults living in the community

Abstract: Background: beat-to-beat technology is increasingly used for investigating orthostatic intolerance (OI) but the prevalence of orthostatic hypotension (OH) diagnosed with this technology is unclear. Objectives: (i) to use beat-to-beat technology to define the prevalence of OH, (ii) to investigate the pathological correlates of OH, (iii) to report the diversity of postural BP responses. Methods: cross-sectional study of adults ≥ 65 years. BP responses to a 3-min head-up tilt were analysed. Results: of 326 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 27 publications
(51 reference statements)
2
34
0
2
Order By: Relevance
“…In contrast, there are many studies in which no association was found between OH and cognitive changes, including community-based studies [1,18,21,24,27,28] and studies in assisted living homes, [21,23,24,27] among hospitalized patients [16,17,36] and among patients in fall clinics. [2,19,25] The present study is more similar, in terms of the composition of the study population (age and co-morbidity) and the prevalence of OH, to studies that were conducted in selected populations of elderly patients with a heavy burden of comorbidity, such as residents in assisted living homes, hospitalized elderly patients, and patients in fall clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, there are many studies in which no association was found between OH and cognitive changes, including community-based studies [1,18,21,24,27,28] and studies in assisted living homes, [21,23,24,27] among hospitalized patients [16,17,36] and among patients in fall clinics. [2,19,25] The present study is more similar, in terms of the composition of the study population (age and co-morbidity) and the prevalence of OH, to studies that were conducted in selected populations of elderly patients with a heavy burden of comorbidity, such as residents in assisted living homes, hospitalized elderly patients, and patients in fall clinics.…”
Section: Discussionmentioning
confidence: 99%
“…MMSE was also used in 8 studies in which no association was found between OH and cognitive impairment. [1,18,22,2528,36] In only one of those studies, [28] the prospective Singapore Longitudinal Aging Study with 2292 participants, was there a statistically significant difference in MMSE score, but after adjusting for relevant variables OH was no longer associated with cognitive state at baseline or with cognitive decline on follow-up. Thus, one can assume that when there is a difference in cognitive state between groups of individuals with and without OH, the difference is not strong enough to be reflected in the MMSE scores.…”
Section: Discussionmentioning
confidence: 99%
“…14 As new methods of phasic BP measurement emerge, phasic BP patterns will require further characterization to enable a better understanding of the clinical impact of abnormal BP behavior. 15 Here, we provide for the first time normative reference data estimated in a population-representative sample for SBP, DBP, and HR responses to active standing, stratified by age and sex and suitable for clinical application. We also propose beat-tobeat definitions and report prevalence estimates of impaired BP stabilization (OH[t]), IOH, and OH.…”
Section: Editorial See P 1772 Clinical Perspective On P 1789mentioning
confidence: 99%
“…One study sampled subjects attending a geriatric day center and reported a prevalence of 72% in fallers and 50% in nonfallers, 20 whereas the second reported a prevalence of 94% in community-dwelling elders. 18 Cooke et al 15 most recently reported a prevalence of 59% in community-dwelling older adults using head-up tilt testing. Again, methodological differences in applying the definition of OH to beat-to-beat measurements likely explain much of the differences here; that is, these studies used any drop of 20/10 mm Hg within 3 minutes of standing to identify those with OH, whereas we included a sustained drop in our definition and estimated the prevalence of OH as 6.9%, a value close to previous oscillometry-based estimates.…”
mentioning
confidence: 99%
See 1 more Smart Citation